Vimentin binds to G-quadruplex repeats found at telomeres and gene promoters. Issue 3 (31st January 2022) - Ceschi, Silvia; Berselli, Michele; Cozzaglio, Marta; Giantin, Mery; Toppo, Stefano; Spolaore, Barbara; Sissi, Claudia
Abstract: G-quadruplex (G4) structures that can form at guanine-rich genomic sites, including telomeres and gene promoters, are actively involved in genome maintenance, replication, and transcription, through finely tuned interactions with protein networks. In the present study, we identified the intermediate filament protein Vimentin as a binder with nanomolar affinity for those G-rich sequences that give rise to at least two adjacent G4 units, named G4 repeats. This interaction is supported by the N-terminal domains of soluble Vimentin tetramers. The selectivity of Vimentin for G4 repeats versus individual G4s provides an unprecedented result. Based on GO enrichment analysis performed on genes having putative G4 repeats within their core promoters, we suggest that Vimentin recruitment at these sites may contribute to the regulation of gene expression during cell development and migration, possibly by reshaping the local higher-order genome topology, as already reported for lamin B.